(untitled) (Research, Society and Development, 2020)
The objective of this study is to know and analyze the course of schooling of graduates of the Pedagogy course of the University of Cuiabá. In order to reach the results, we used the methodological approach of the narratives whose instrument of data collection and analysis of the results was the narrative interview anchored in Souza (2006) and Connelly and Clandinin (2011, page 48). Empirical data pointed out that during the academic course, they were affected by emotional overload due to the need to comply with the requirements of the academy, since the academic life requires dedication, as well as extraclass activities that are necessary to fulfill the course. The narratives produced by the teachers pointed out that academic life was an instrument for professional achievement and revealed as an element of reflection on teacher education, awareness of their own practice including reflection, evaluation and improvement of teaching work. The results also pointed out that the Pedagogy course made possible the contact with the learning during the stage, with the theory during the formation period, besides the exchange of knowledge with the classmates, constructing significant elements that resulted in the teacher training, strengthening the meaning of what it is to be a teacher.